Peningkatan Hasil Belajar Siswa Dengan Menggunakan Pendekatan Problem Based Learning (PBL) pada Pembelajaran PKn di Kelas IV SDN 11 Kunangan Parit Rantang Kecamatan Kamang Baru - Penti Suryani (Warta Pendidikan | e-Journal, 2020)
Based on the experience felt in grade IV SD Negeri 11 Kunangan Parit Rantang shows that Civics learning is still carried out conventionally where teachers still use learning media that is limited to textbooks and learning assessment is only in the cognitive domain. This causes students to be less active in the learning process and the learning outcomes they get are low. To improve the learning outcomes of students in Civics learning, classroom action research was conducted. The purpose of this study is to describe how the design, implementation and assessment of Civics learning using the Problem Based Learning (PBL) approach. This research is a classroom action research with qualitative and quantitative approaches. In practice, this study consisted of two cycles conducted collaboratively with Civics teachers. Each cycle consists of planning activities, implementing actions accompanied by observation and reflection in each cycle. This research was conducted in the second semester of the 2018/2019 academic year at SD Negeri 11 Kunangan Parit Rantang with the research subjects being all the fourth grade students of the researched elementary school. The research data were obtained through observation, interviews, field notes, documentation and test results. The results of the research data analysis showed that the use of the Problem Based Learning (PBL) approach media could improve student learning outcomes in Civics learning in class IV SD Negeri 11 Kunangan Parit Rantang. This can be seen from (1) the learning outcomes of students in the cognitive realm increased from an average value of 71.5 in cycle I to 89 in cycle II, (2) in the affective domain increased from an average value of 66 in cycle I to 94 in cycle II and (3) in the psychomotor domain increased from an average value of 73 in cycle I to 95 in cycle II. Seeing the results of this study, classroom action research using the Problem Based Learning (PBL) approach in Civics learning needs to be applied and developed in order to improve the quality of education in the future.